Incidence of Sociocultural Determinants in Health Interventions in the Embera Community, Colombia - Bautista Gómez, Martha Milena (2025)
The inequality in access to health is one of the great challenges in health that disproportionately affects the most vulnerable social groups. In Pueblo Rico (Colombia), there is a wide inequality in access to and quality of health that disproportionately affects the indigenous population. This study aims to understand the social determinants that affect the health of this population, in terms of territorial, social, economic, and cultural limitations; and to elucidate which of these factors are possible to intervene in order to contribute to greater equity in health. It was found that the health of the Embera population is affected by complex socio-spatial segregation, high vulnerability due to factors of exclusion, poverty, and violence, and cultural conflicts due to the lack of recognition and unequal power structures. These conditions make it a very complex community to intervene, so it requires differential and culturally adapted health interventions that favor the inclusion of the most vulnerable groups and that promote the development of capacities of the population through appropriate health interventions.